Orientation of prehistoric monuments in Britain - Marshall, Alistair J. (Oxford)
xxxiv, 661 sayfa
Keywords: “Orientation of Prehistoric Monuments in Britain: A Reassessment' views the type of major axial alignment seen at many megalithic ritual and funerary monuments of Neolithic to Bronze Age date in Britain and Ireland, not in terms of more abstract astronomical concerns, but rather as an expression of repeated seasonal propitiation, basically solar, involving community, agrarian economy, and the ancestors in a combined attempt to mitigate variable environmental conditions. The analysis is supported by over 800 images, open-source, for unrestricted use, and available digitally.” --